Peer Assessment in Writing Classroom: Exploring its Potential in Developing Students Communication Skills - Rogti, Maroua (Journal of Language and Literature Studies, 2025)
In higher education in Algeria, assessment in the English as a Foreign Language classroom remains a contentious issue, as educators continue to express skepticism towards the adoption of the new assessment paradigm. In this regard, stakeholders successfully implemented alternate evaluation methods to evaluate students’ performance more accurately. This research aims to investigate the importance of genuine assessment, specifically peer evaluation, in the EFL writing classroom. A quantitative technique was used for the research, including a survey delivered to a randomly chosen sample of forty (40) EFL students at ENS of Laghouat. The study used descriptive statistics and regression analysis. The results confirmed that most students possess favorable attitudes towards peer assessment, as it enhances their self-reflection by incorporating real-life experiences and providing them with a degree of control over their learning through tasks, thereby fostering greater responsibility and independence in their learning process. Students may encounter challenges when participating in peer assessment in their writing classroom. However, they have the capacity for self-regulation and can develop greater awareness and responsibility for their own learning.